Correlation and Path Analysis for Yield and Yield Component Traits on Bread Wheat (Triticum aestivum L.) Genotypes - Zewdu, Demeke; Mekonnen, Fikru; Geleta, Negash (International Journal of Bio-resource and Stress Management, 2024)
The research was conducted at Kulumsa Agricultural Research Center Main Station, during July–November, 2021 (Main cropping season) to study the association among traits and estimate the direct and indirect effects of various traits on grain yield of bread wheat genotypes. A total of 64 bread wheat genotypes were evaluated for 16 traits in 8×8 simple lattice design. Grain yields showed positive and highly significant at (p<0.01) genotypic and phenotypic correlation with plant height, number of seeds spike-1, head weight, yield head-1, biomass yield, hectoliter weight, test weight and harvest index. Genotypic correlation coefficients were greater for all significantly correlated with grain yield studied traits than the corresponding phenotypic correlation coefficients, indicating inherent association of the characters, therefore, selection for these characters could improve grain yield. Genotypic path analysis of the direct effects revealed that days to maturity, number of spikelets spike-1, head weight, yield head-1, biomass yield, hectoliter weight, test weight and harvest index exerted direct positive effect on grain yield. Phenotypic path analysis of the direct effects showed that days to maturity, plant height, number of tillers plant-1, number of seeds spike-1, head height, yield head-1, biomass yield, test weight and harvest index had direct positive effect on grain yield. Therefore, these traits should be considered for bread wheat breeding program for yield improvement.